The role of social work in mental health and academic performance of students. (2022)
Social workers have an important role in the field of mental health, and social work programs have a responsibility to prepare students for practice in the field. However, it seems that various societies, groups and individuals have questioned the role of social workers in mental health. An increasing number of students entering university are identifying themselves as having mental health issues and those with higher levels of cumulative trauma tend to have more difficulty adjusting personally and emotionally to the transition, and abuse is linked to an increased probability of dropping out of collegeas well as to increased rates of depression and suicide. This paper examines the role of social workers in mental health and academic performance of students. Social workers have a key role in helping community participation and engagement, alongside other primary healthcare workers in delivering mental health support. It is recommended that activities such as case scenarios and role plays be used to prepare the student first, and that students be given the opportunity to practice these skills in actual practice settings as well. School authorities should not wait or watch till a student academic performance degrade totally before he or she is handed to a social worker with mental health experience. Periodic sessions should be organized by school authorities to gauge student mental stability from time to time to avoid any epidemic of mental breakdown which in tum affects their academic performance.